2018
DOI: 10.1007/s00128-018-2286-8
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Oxidative Stress and Cellular Deformities in Clarias gariepinus (Burchell) from River Yamuna in Delhi Region, India

Abstract: River Yamuna is under constant menace due to pollution levels beyond limit, ensuing chronic poisoning of aquatic biota. Induction of oxidative stress and cellular deformities is a common effect in fish. The present study aimed in assessing impact of environmental pollutants on gonad (testis) of Clarias gariepinus from Wazirabad barrage (entry site) and Okhla barrage (exit site) of river Yamuna in Delhi segment. Antioxidant enzymes assays viz. Super oxide dismutase (SOD), catalase (CAT) and ferric reducing anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The recorded testicular damages and testicular oocytes appearance may be caused by an imbalance between apoptosis and testicular cell proliferation in addition to the inhibitory effects of EDCs on spermatogenesis in fish. Oxidative stress and excessive ROS production may cause several genotoxic, histological, and reproductive disorders via extra-gonadal or gonadal alterations (Tyor and Pahwa 2018;Abdel-Khalek et al 2020b, 2021b. Therefore, the antioxidant defense components have a protective role in gonads via activation of several compensatory mechanisms against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recorded testicular damages and testicular oocytes appearance may be caused by an imbalance between apoptosis and testicular cell proliferation in addition to the inhibitory effects of EDCs on spermatogenesis in fish. Oxidative stress and excessive ROS production may cause several genotoxic, histological, and reproductive disorders via extra-gonadal or gonadal alterations (Tyor and Pahwa 2018;Abdel-Khalek et al 2020b, 2021b. Therefore, the antioxidant defense components have a protective role in gonads via activation of several compensatory mechanisms against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the potential consequences of EDCs, the histological examination of gonads must be recognized to monitor structural modifications since the external examination can often make these altered gonads appear normal. As reported by Tyor and Pahwa (2018), the oxidative stress condition and unscavenged ROS may initiate gonadal deformities and lead directly to male infertility in fish. Therefore, assessing the integrated enzymatic (ex: catalase and superoxide dismutase) and non-enzymatic (ex: glutathione reduced and thiobarbituric acid reactive substances) antioxidant biomarkers have been used in several toxicological studies (Samanta et al 2018;Abdel-Khalek et al 2021a).…”
mentioning
confidence: 90%
“…Oxidative stress followed by respiratory stress and genotoxicity would further disrupt steroidogenic activity in gonads. Recently, Tyor et al (2018) reported testicular oxidative stress and cellular deformities in Clarias gariepinus (Burchell) from River Yamuna in Delhi region. In rats, Nonylphenol leads to serious testicular dysfunction and induces cell death (Cardinali et al, 2004).…”
Section: O P Ymentioning
confidence: 99%